2019
DOI: 10.3390/cells8121612
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethylene on Cell Wall and Lipid Metabolism during Alleviation of Postharvest Chilling Injury in Peach

Abstract: Peach is prone to postharvest chilling injury (CI). Here it was found that exogenous ethylene alleviated CI, accompanied by an increased endogenous ethylene production. Ethylene treatment resulted in a moderately more rapid flesh softening as a result of stronger expression of genes encoding expansin and cell wall hydrolases, especially xylosidase and galactosidase. Ethylene treatment alleviated internal browning, accompanied by changes in expression of polyphenol oxidase, peroxidase and lipoxygenases. An enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 79 publications
(114 reference statements)
1
24
0
Order By: Relevance
“…3,8 In climacteric fruit, ethylene production enhances the expression of some regulatory and structural genes that do not act to regulate ripening in isolation but rather act in concert with other plant hormones. 11,36 In this study, most auxin-related genes were downregulated at the protein level in ripening kiwifruits, including IAR3, ILL3, ARG1, SNX2b, ATB2, and AIR9, whereas AIR12 was strongly upregulated (Figure 4A,C). Hence, speculations regarding potential connections need to be further validated.…”
Section: ■ Resultssupporting
confidence: 71%
“…3,8 In climacteric fruit, ethylene production enhances the expression of some regulatory and structural genes that do not act to regulate ripening in isolation but rather act in concert with other plant hormones. 11,36 In this study, most auxin-related genes were downregulated at the protein level in ripening kiwifruits, including IAR3, ILL3, ARG1, SNX2b, ATB2, and AIR9, whereas AIR12 was strongly upregulated (Figure 4A,C). Hence, speculations regarding potential connections need to be further validated.…”
Section: ■ Resultssupporting
confidence: 71%
“…Ethylene is a phytohormone induced by various factors such as microbial pathogens, insect attacks, and stimuli. This phytohormone regulates a wide range of physiological processes, including fruit ripening and metabolite pathway activation [ 12 , 13 ]. Recent literature has proven that soybean proteins provide health benefits, such as blood cholesterol reduction, protection against coronary heart disease, and anti-obesity properties [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that in melting peach fruit, ethylene biosynthesis [ 2 , 11 , 12 ], lipid metabolism [ 13 ], and cell wall metabolism [ 10 ] are related to CI. Previous studies have shown that exogenous ethylene affects fruit softening and membrane fluidity by regulating the expression of cell wall- and lipid metabolism-related genes, thus reducing the Cl symptoms in peach fruit [ 14 ]; however, the molecular mechanism of ethylene biosynthesis under cold stress and the direct relationship between endogenous ethylene level and fruit softening and lipid metabolism have not yet been explored. Although stony hard (SH) peach fruit usually changes color and contains a high content of soluble solids at ripening, they do not release ethylene, and the mature pulp is very hard and brittle, both on and off the tree [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%